Personalising the evaluation of substance misuse treatment: A new approach to outcome measurement - Alves, Paula (2018)
Patient involvement in healthcare, in general, and in substance misuse in particular, has become a topic of paramount importance (Rutter et al., 2004). Patient involvement can be conceptualised as listening to the patients’ perspective and encouraging patients to take an active role in the care they are receiving. This approach is advocated by international authorities in health and social care such as the United Kingdom’s NICE, which recommends “person-centred care” that takes into account the patient’s “needs, preferences and strengths” (Crawford, 2011). According to Orford (2008), the perspectives of patients in substance misuse treatment tend to be overlooked and their involvement with treatment is limited